Challenges in the use of the treat-to-treat strategy in atopic dermatitis in Latin America: A case series review (2023)
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic, relapsing-remitting illness. In moderate-to-severe instances, recommendations urge patient-centered systemic therapy. Existing standards lack long-term treatment success requirements. A treat-to-target methodology was proposed for systemic therapy patients that requires global improvements to prompt decisions about treatment. Methods: We conducted an observational study between May 2021 and June 2022 in three Ecuadorian patients with severe AD who were treated with dupilumab to assess the clinical evolution and behavior of the subdomains evaluated by clinimetric tools. Results: Patients A and C satisfied disease-domain response criteria to dupilumab at 12 and 24 weeks, but B did not complete the algorithm objectives. Nonetheless, patient A improved AD severity, itching, bleeding, desquamation, sleep, daily activities, mood, emotions, sexual troubles, clothing, and sports subdomains. Patient B experienced reduced symptomatology, AD aggravation, daily activities impact, and work/study impairment. Patient C improved from severe to mild desquamation, itching, exudate, lichenification, and rough/dry skin. Sleep, shame, and study subdomains improved the most. Conclusion: We provide a new operational construct for analyzing current patient-reported outcome measures (PROMs) and clinician-reported outcome measures (CROMs) based on subdomains to widen our understanding of the state of disease activity and make clinical decisions when the treat-to-target strategy is not attained.